An analysis of youth unemployment in the euro area - Ramon Gomez-Salvador; Nadine Leiner-Killinger (European Central Bank (ECB), 2008)
The paper starts by presenting some stylised facts on youth unemployment over the last two decades, both at the euro area and the country level. It shows that despite declining considerably over the last few years, youth unemployment has remained at a high level relative to other age groups in most euro area countries. The paper finds that there is a positive relationship between the share of young people in the total population and the youth unemployment rate, i.e. the smaller the share of young people in the population, the lower the risk of them being unemployed. At the same time, economic conditions are negatively correlated with the youth unemployment rate, i.e. the youth unemployment rate increases when the economic situation worsens. Moreover, robust results across the regression scenarios show that higher employment protection and minimum wages imply a higher youth unemployment rate, while active labour market policies (ALMPs) tend to reduce it. The results also indicate that the increasing share of services employment in total employment is helping to reduce unemployment among young persons. Furthermore, the increase in the youth inactivity rate, which is mainly due to the fact that there are more young people in education, is also linked to the overall decline in youth unemployment. Finally, as regards education, the results indicate that the number of years of education, the number of young people with vocational training and, to a lesser extent high scores in the PISA study, are associated with lower youth unemployment rates. The share of the young population not in school, however, is positively correlated with the unemployment rate. As youth unemployment is subject to certain country-specific features, each country should identify the relevant underlying sources of youth unemployment and react accordingly. Governments can make a positive contribution to the smooth transition of young persons fromeducation to the labour market by providing a well-functioning education system and labour market institutions that do not introduce distortions into the labour market.
Keywords: I2; J11; J13; J21; J64; 330; Youth; unemployment; employment; demographic trends; institutions; education.; Jugendarbeitslosigkeit; Arbeitsmarkt; Berufsbildung; Altersstruktur; Arbeitsverwaltung; EU-Staaten